2016
DOI: 10.1111/ijlh.12616
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of rare BCRABL1 fusion transcripts in chronic myeloid leukemia patients

Abstract: Characterization of the specific fusion transcript in CML patients is important owing to the difference in prognosis and response to therapy in addition to the conventional need for monitoring treatment response. CML patients with e1a2 transcripts have to be closely monitored due to the high incidence of disease progression and treatment resistance/failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 35 publications
(47 reference statements)
3
23
0
Order By: Relevance
“…A vast majority of CML patients have the typical e13a2 and/or e14a2 BCR‐ABL1 junction. Several studies with large sample sizes have shown that the frequency of the common e13a2/e14a2 transcript in CML was 97·7% to 98·5% (Ito et al , ; Goh et al , ; Todoric‐Zivanovic et al , ; Arun et al , ), consistent with our findings (98·3%). The e1a2, e19a2 and e13a3/e14a3 transcripts were the most commonly reported types in previous studies (Goh et al , ; Arun et al , ) and the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A vast majority of CML patients have the typical e13a2 and/or e14a2 BCR‐ABL1 junction. Several studies with large sample sizes have shown that the frequency of the common e13a2/e14a2 transcript in CML was 97·7% to 98·5% (Ito et al , ; Goh et al , ; Todoric‐Zivanovic et al , ; Arun et al , ), consistent with our findings (98·3%). The e1a2, e19a2 and e13a3/e14a3 transcripts were the most commonly reported types in previous studies (Goh et al , ; Arun et al , ) and the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies with large sample sizes have shown that the frequency of the common e13a2/e14a2 transcript in CML was 97·7% to 98·5% (Ito et al , ; Goh et al , ; Todoric‐Zivanovic et al , ; Arun et al , ), consistent with our findings (98·3%). The e1a2, e19a2 and e13a3/e14a3 transcripts were the most commonly reported types in previous studies (Goh et al , ; Arun et al , ) and the present study. In addition to these 3 types of transcripts, we identified e1a3, e6a2, e8a2, e12a2 and unusual e13a2/e14a2 and found that the three most frequent types accounted for three‐quarters of the cases with uncommon BCR‐ABL1 transcripts.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The incidence rates of the BCR‐ABL1 transcript types gathered from the full‐text articles are given in Table . Of 26 articles, 22 (85%) showed a higher incidence of the e14a2 transcript whereas only 4 articles demonstrated a higher incidence of the e13a2 transcript.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conclusions of these studies are limited by the low number of patients. 5, 8, 9 To investigate the significance of the e1a2 transcript subtype, we examined a cohort of 2322 CML patients treated with tyrosine kinase inhibitors (TKIs), and analyzed the frequency, risk of blastic transformation, treatment response and outcomes of patients with this transcript subtype.…”
mentioning
confidence: 99%